An Experiment on Flashing-Spray Jet Characteristics of Supercritical CO2 from Various Orifice Geometries - Teng, Lin; Bai, Jinbao; Li, Yuxing; Wang, Cailin (Frontiers in Energy Research, 2021)
Supercritical CO2 pipelines usually are used to link the CO2 capture system to the geological storage. There are severe hazards once the asphyxiating gas leaks from the long-distance pipeline. The uncertainty of near-field jet characteristics results in imprecise consequences assessment of accidental release of supercritical CO2. To improve the prediction of consequences of accidental release accuracy, the near-field mechanisms of flashing-spray jet was investigated. In this work, an experimental setup with multiple measurement instruments was developed to impose controllable CO2 release from a high-pressure vessel. The flashing-spray jet structures of supercritical CO2 from circular and rectangular orifices were recorded by a high-speed camera. Results indicate that the near-field structures of supercritical CO2 jet from circular and rectangular orifices are totally different, which causes the different dispersion consequences. The jet angle and shock waves were analyzed quantitatively. Lastly, the models of flashing-spray based on the two different phenomena from rectangular and circular orifices were discussed. The combination of macroscopic and microscopic data in the jet can help to understand the complex physics and improve discharge and dispersion model. This work provides a fundamental data to consequences assessment of accidental release of supercritical CO2.